RNAi in Piezodorus guildinii (Hemiptera: Pentatomidae): Transcriptome Assembly for the Development of Pest Control Strategies - Schvartzman, Claudia; Fresia, Pablo; Murchio, Sara; Mujica, María Valentina; Dalla-Rizza, Marco (Frontiers in Plant Science, 2022)
Red-banded stink bug Piezodorus guildinii (P. guildinii) has been described as the most damaging stink bug regarding soybean crops, leading to seed injury, low germination percentages and foliar retention even at low population densities. In the recent years, RNA interference (RNAi), a conserved eukaryote mechanism of post-transcriptional silencing has been explored to develop species-selective pesticides. In this work we evaluated RNAi in P. guildinii to develop new pest control strategies. For this, we assembled and annotated a P. guildinii transcriptome from a pool of all developmental stages. Analysis of this transcriptome led to the identification of 56 proteins related to the silencing process encompassing siRNA, miRNA and piRNA pathways. To evaluate the functionality of RNAi machinery, P. guildinii adults were injected with 28ng per mg of body weight of dsRNA targeting vATPase A. A mortality of 35% and 51.6% was observed after 7 and 14 days respectively and a downregulation of vATPase A gene of 84% at 72h post injection. In addition, Dicer-2 and Argonaute-2 genes, core RNAi proteins were upregulated 1.8 fold at 48h after injection. These findings showed for the first time, that RNAi is functional in P. guildinii and the silencing of essential genes has a significant effect in adult viability. Taken together, the work reported here shows that RNAi could be an interesting approach for the development of control strategies of the red-banded stink bug.